Prospective multicentre clinical study on inter- and intrapatient genetic variability for antimicrobial resistance of Helicobacter pylori. (March 2018) - Bilgilier, C.; Stadlmann, A.; Makristathis, A.; Thannesberger, J.; Kastner, M.-T.; Knoflach, P.; Steiner, P.; Schöniger-Hekele, M.; Högenauer, C.; Blesl, A.; Datz, C.; Huber-Schönauer, U.; et al.
Abstract: Objectives: We report on a large prospective, multicentre clinical investigation on inter- and intrapatient genetic variability for antimicrobial resistance of Helicobacter pylori . Methods: Therapy-naive patients ( n  = 2004) who had undergone routine diagnostic gastroscopy were prospectively included from all geographic regions of Austria. Gastric biopsy samples were collected separately from antrum and corpus. Samples were analysed by histopathology and real-time PCR for genotypic resistance to clarithromycin and quinolones. Clinical and demographic information was analysed in relation to resistance patterns. Results: H. pylori infection was detected in 514 (26%) of 2004 patients by histopathology and confirmed in 465 (90%) of 514 patients by real-time PCR. PCR results were discordant for antrum and corpus in 27 (5%) of 514 patients, indicating inhomogeneous infections. Clarithromycin resistance rates were 17% (77/448) and 19% (84/455), and quinolone resistance rates were 12% (37/310) and 10% (32/334) in antrum and corpus samples, respectively. Combination of test results per patient yielded resistance rates of 21% (98/465) and 13% (50/383) for clarithromycin and quinolones, respectively. Overall, infection with both sensitive and resistant H. pylori was detected in 65 (14%) of 465 patients. Conclusions: Anatomically inhomogeneous infection with different, multiple H. pylori strains is common. Prospective clinical study design, collection of samples from multiple sites and microbiologic methods that allow the detection of coinfections are mandatory for collection of reliable data on antimicrobial resistance patterns in representative patient populations. (ClinicalTrials.gov identifier:NCT02925091 ).